2010
DOI: 10.1177/016146811011200303
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of the Effects of Early Education Interventions on Cognitive and Social Development

Abstract: Background/Context There is much current interest in the impact of early childhood education programs on preschoolers and, in particular, on the magnitude of cognitive and affective gains. Purpose/Objective/Research Question/Focus of Study Because this new segment of public education may require substantial resources, accurate descriptions are required of the potential benefits and costs of implementing specific preschool programs. To address this issue comprehensively, a meta-analysis was conducted for the pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
94
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 550 publications
(123 citation statements)
references
References 50 publications
5
94
1
5
Order By: Relevance
“…These estimated effects of Head Start on children's development, especially cognitive outcomes after 1-year participation in the HSIS, were smaller compared with those reported in earlier evaluations of model early interventions (e.g., Perry Preschool, Abecedarian, and the Infant Health and Development Program [IHDP]; with short-term effect sizes of 0.35-0.97 on cognitive outcomes) (Brooks-Gunn, 2011;Camilli et al, 2010;Karoly, Kilburn, & Cannon, 2005;Ludwig & Phillips, 2007). This difference may reflect the fact that the counterfactual has changed, given that few 3-and 4-year-old children in the 1960s to the 1980s attended any form of preschool if they did not have Head Start or other model early interventions evaluated in many prior studies while most of these age-groups of children today have some form of school-or center-based care (Waldfogel, 2006).…”
Section: Background and Literature Reviewcontrasting
confidence: 57%
“…These estimated effects of Head Start on children's development, especially cognitive outcomes after 1-year participation in the HSIS, were smaller compared with those reported in earlier evaluations of model early interventions (e.g., Perry Preschool, Abecedarian, and the Infant Health and Development Program [IHDP]; with short-term effect sizes of 0.35-0.97 on cognitive outcomes) (Brooks-Gunn, 2011;Camilli et al, 2010;Karoly, Kilburn, & Cannon, 2005;Ludwig & Phillips, 2007). This difference may reflect the fact that the counterfactual has changed, given that few 3-and 4-year-old children in the 1960s to the 1980s attended any form of preschool if they did not have Head Start or other model early interventions evaluated in many prior studies while most of these age-groups of children today have some form of school-or center-based care (Waldfogel, 2006).…”
Section: Background and Literature Reviewcontrasting
confidence: 57%
“…In contrast, it is not clear that this presumption is met in many preschool classrooms (Greenwood et al, 2011(Greenwood et al, , 2013. Although there is evidence that preschool can have positive effects on the readingrelated skills of young children (e.g., Campbell, Ramey, Pungello, Sparling, & Miller-Johnson, 2002;Gormley, Phillips, & Gayer, 2008;Wong, Cook, Barnett, & Jung, 2008), there is both limited evidence for the efficacy of most preschool curricula (Camilli, Vargas, Ryan, & Barnett, 2010;Lonigan & Cunningham, 2013) and limited evidence that most preschool settings are implementing the select number of efficacious Tier I curricula. Regarding the efficacy of curricula, the U.S. Department of Education's What Works Clearinghouse's (WWC) reported that of more than 60 commercially available literacy or comprehensive preschool curricula, only 13 had studies that met evidence standards for causal interpretation; of these, only five curricula had evidence of a positive impact on one or more literacy-related skill.…”
Section: Core Classroom Curriculum In Preschoolmentioning
confidence: 99%
“…Encouraged by the supportive approach of the teachers, this attitude toward kindergarten is the basis for future attitudes toward education in general and thus, in a broader perspective, influences future motivation for school achievement ( Fuhs et al, 2013 ; Stephanou, 2014 ; Daviran, 2015 ). This effect is even more important for children from disadvantaged or unstimulating backgrounds, where kindergarten can play an important role in eliminating these deficits ( Currie, 2001 ; Duncan et al, 2007 ; Camilli et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%